Hydrogen Peroxide Promotes Tomato Leaf Senescence by Regulating Antioxidant System and Hydrogen Sulfide Metabolism - Yue Yu; Siyue Wang; Wentong Guo; Meihui Geng; Ying Sun; Wanjie Li; Gaifang Yao; Danfeng Zhang; Hua Zhang; Kangdi Hu (Plants, 2024)
Hydrogen peroxide (H2O2) is relatively stable among ROS (reactive oxygen species) and could act as a signal in plant cells. In the present work, detached tomato leaves were treated with exogenous H2O2 at 10 mmol/L for 8 h to study the mechanism of how H2O2 regulates leaf senescence. The data indicated that H2O2 treatment significantly accelerated the degradation of chlorophyll and led to the upregulation of the expression of leaf senescence-related genes (NYC1, PAO, PPH, SGR1, SAG12 and SAG15) during leaf senescence. H2O2 treatment also induced the accumulation of H2O2 and malondialdehyde (MDA), decreased POD and SOD enzyme activities and inhibited H2S production by reducing the expression of LCD1/2 and DCD1/2. A correlation analysis indicated that H2O2 was significantly and negatively correlated with chlorophyll, the expression of leaf senescence−related genes, and LCD1/2 and DCD1/2. The principal component analysis (PCA) results show that H2S showed the highest load value followed by O2•−, H2O2, DCD1, SAG15, etc. Therefore, these findings provide a basis for studying the role of H2O2 in regulating detached tomato leaf senescence and demonstrated that H2O2 plays a positive role in the senescence of detached leaves by repressing antioxidant enzymes and H2S production.